Perinatální paliativní péče a její vnímání pečujícími profesemi v perinatologickém centru - Kopecký, Ondřej; Šlegerová, Lenka; Dušek, Pavel; Paslerová, Ráchel; Macová, Iva; Rusinová, Kateřina (Paliativní medicína, 2024)
Pediatric and perinatal palliative care development has received particular attention in the Czech Republic in recent years. As part of the cooperation project of clinics in developing comprehensive care in the perinatal period, this area has been the focus of attention in the Perinatology Intensive Care Centre at the General University Hospital in Prague. In addition to broad educational activities, a questionnaire study with two parts – semi-quantitative and qualitative – was conducted to describe the respondents' perceptions of the importance of perinatal palliative care topics and assess their practice in providing care. Respondents to the questionnaire PRIMA were from various professions and leadership roles in different departments and across specialties in the perinatology center.